Penerapan Teknologi Pirolisis Untuk Konversi Limbah Plastik Menjadi Bahan Bakar Minyak di Kabupaten Bantul - Ricki Rafli; Hudi Baitul Fajri; Ahmad Jamaludhin; Muhammad Azizi; Haris Riswanto; Mochamad Syamsiro (Jurnal Mekanika dan Sistem Termal, 2017)
Plastic waste is an inorganic waste composed of chemicals that are harmful to the environment because it is not easy to decompose in the soil and requires decades to decompose. Therefore, it needs to do further processing by converting waste plastics into valuable products. This study aims to implement the pyrolysis technology to convert waste plastics into fuel oil which can be used as an energy source for small and medium enterprise. This technology has been applied in Bank Sampah Mekar Jaya 8, one of the recycling bank in Bantul Regency. This system is expected to empower the community for getting added value from waste plastics. The pyrolysis reactor was made with a production capacity of 20 kg. The reactor has a diameter of 600 mm and height of 900 mm with 2 main holes used to feed waste plastics and remove the residue. The system used 2 condensers which has a diameter of 100 mm respectively. The second condenser employed double pipe heat exchanger system which use water as a cooling medium. The water pump has been used for water circulation in the second condenser.